Thickener

A methacrylic resin with controlled molecular weight and particle diameter, produced via one-stage suspension polymerization, addresses solubility and pump-up issues in artificial marble production, enhancing productivity and reducing costs while maintaining product quality.

JP7608575B2Active Publication Date: 2025-01-06ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023201896
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-18
Filing Date
2023-11-29
Publication Date
2025-01-06
Estimated Expiration
2040-05-13

AI Technical Summary

Technical Problem

Existing methacrylic resin thickeners used in artificial marble production have solubility issues, leading to prolonged syrup preparation times, increased costs, and potential pump-up failures during slurry transfer, affecting the color tone and mechanical strength of the final product.

Method used

A methacrylic resin with controlled molecular weight, particle diameter, and particle diameter variation is produced through one-stage suspension polymerization, ensuring easy solubility, improved viscosity, and resistance to pump-up failures, while maintaining mechanical strength and color tone.

Benefits of technology

The solution results in a thickener that shortens syrup preparation time, enhances productivity, and reduces production costs without compromising the mechanical strength and color tone of artificial marble, while preventing pump-up failures during slurry transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608575000001
    Figure 0007608575000001
  • Figure 0007608575000002
    Figure 0007608575000002
Patent Text Reader

Abstract

To provide a thickener which can be easily dissolved in methyl methacrylate and can apply a predetermined viscosity as a syrup, and which has excellent color tone of the syrup and causes less poor pump-up during transportation of a slurry.SOLUTION: A thickener of the invention includes a methacryl resin in which Mw / Mn is 1.7-2.5, a mean particle diameter is 150-250 μm and a standard deviation of particle diameter is 40-150 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thickening agent. [Background technology]

[0002] Generally, artificial marble is obtained by heating and polymerizing a syrup containing added silica or aluminum hydroxide. The syrup is a liquid in which methacrylic resin is dissolved in methyl methacrylate. The methacrylic resin is dissolved in the syrup as a thickener to increase the viscosity of the syrup and make it easier to handle. The molecular weight of the methacrylic resin used as a thickener is often about 150,000 to 200,000. However, since methacrylic resin does not easily dissolve in methyl methacrylate, it is melted over several hours while applying heat. Therefore, the time required to make artificial marble, which consists of the time required to prepare the syrup and the time required to heat and polymerize the syrup, is long, which raises the total manufacturing cost. Therefore, there is a need to develop a thickener that can shorten the preparation time of syrup while maintaining the heat resistance and mechanical strength of conventional artificial marble, or a thickener that can be added in a reduced amount to the syrup.

[0003] A thickener made of a specific methacrylic resin is disclosed in Patent Document 1. The methacrylic resin is obtained by two-stage suspension polymerization, and is described as having excellent solubility in methyl methacrylate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2008-174574 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the methacrylic resin used in the thickener described in Patent Document 1 is obtained by two-stage suspension polymerization, which results in a large amount of suspension agent being entrained, and there was a problem that when used as a thickener, the color tone of the obtained syrup becomes poor. Furthermore, when the particle size of the methacrylic resin beads prepared by suspension polymerization is reduced, there is a problem in that pump-up failure occurs during slurry transfer in the bead filtration process.

[0006] Therefore, an object of the present invention is to provide a thickener which is easily soluble in methyl methacrylate, can impart a predetermined viscosity to the syrup, has excellent color tone, and is less likely to cause pump-up problems when transporting the slurry during production. [Means for solving the problem]

[0007] In order to solve the above problems, the inventors conducted extensive research and, as a result, they surprisingly discovered that when methacrylic resin is formed into beads and used as a thickener with the average particle size and particle size variation controlled within specific ranges, the solubility in methyl methacrylate is improved, increasing the production efficiency of the syrup, and when made into artificial marble, the syrup exhibits mechanical strength, durability, and color tone equivalent to conventional products. They have thus completed a thickener that can reduce production costs and a method for producing the same.

[0008] That is, the present invention is as follows. [1] A thickener comprising a methacrylic resin having an Mw / Mn ratio of 1.7 to 2.5, an average particle size of 150 to 250 μm, and a standard deviation of the particle size of 40 to 150 μm. [2] The thickener according to [1], wherein the Mw of the methacrylic resin is 85,000 to 500,000. [3] The thickener according to [1] or [2], wherein the methacrylic resin contains 100 to 80 mass % of methyl methacrylate monomer units and 0 to 20 mass % of other vinyl monomer units copolymerizable with methyl methacrylate. [4] The thickener according to any one of [1] to [3], wherein the 10% particle size D10 of the methacrylic resin is 50 μm to 130 μm. [5] The thickener according to any one of [1] to [4], wherein the aluminum content in the methacrylic resin is 1 ppm by mass or more and 50 ppm by mass or less. [6] A method for producing a thickener according to any one of [1] to [5], comprising a step of producing a methacrylic resin by one-stage suspension polymerization. [7] A method for producing a thickener according to any one of [1] to [5], comprising a step of dispersing a suspending agent having an average particle size of 10 to 40 μm in water and polymerizing the same. [8] A method for using a thickener, comprising using the thickener according to any one of [1] to [5]. Effect of the Invention

[0009] The thickener according to the present invention is easily soluble in methyl methacrylate, can impart a desired viscosity to the syrup, has excellent syrup color, and is less likely to cause pump-up failures when transporting the slurry during production. Furthermore, the syrup can be prepared in a short time, improving syrup productivity, and the artificial marble obtained by thermally polymerizing the syrup can maintain the conventional mechanical strength and durability. In addition, the thickener can prevent pump-up failure during slurry transfer in the bead filtration process during suspension polymerization, improving productivity. In addition, the thickener can reduce the cost of preparing syrup, making it possible to provide artificial marble at a lower price than before. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment for carrying out the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be carried out in various modifications within the scope of the gist of the present invention.

[0011] [Thickener] The thickener of the present embodiment contains a methacrylic resin having an Mw / Mn ratio of 1.7 to 2.5, an average particle size of 150 to 250 μm, and a standard deviation of the particle size of 40 to 150 μm. The thickener may be a mixture further containing other methacrylic resin compositions as impurities, but is preferably composed only of the methacrylic resin.

[0012] (Methacrylic resin) The methacrylic resin is a homopolymer made of a methyl methacrylate monomer, or a copolymer made of a methyl methacrylate monomer and at least one other vinyl monomer copolymerizable with methyl methacrylate.

[0013] Examples of the other vinyl monomers copolymerizable with methyl methacrylate include alkyl methacrylates having an alkyl group with 2 to 18 carbon atoms, and alkyl acrylates having an alkyl group with 1 to 18 carbon atoms; α,β-unsaturated acids such as acrylic acid and methacrylic acid, unsaturated group-containing divalent carboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and their alkyl esters; aromatic vinyl compounds such as styrene, α-methylstyrene, and styrene having a substituent on the benzene ring; cyanide vinyl compounds such as acrylonitrile and methacrylonitrile; maleic anhydride, maleimide, and N-substituted maleimide; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, and the like. Examples of the acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof whose both terminal hydroxyl groups are esterified with acrylic acid or methacrylic acid; neopentyl glycol di(meth)acrylate, di(meth)acrylate, and other two alcohol hydroxyl groups are esterified with acrylic acid or methacrylic acid; trimethylolpropane, pentaerythritol, and other polyhydric alcohol derivatives are esterified with acrylic acid or methacrylic acid; and polyfunctional monomers such as divinylbenzene; and the like. These can be used alone or in combination of two or more. Among these, from the viewpoints of light resistance, heat stability, heat resistance, and fluidity, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, 2-ethylhexyl acrylate, and the like are preferably used. Methyl acrylate, ethyl acrylate, and n-butyl acrylate are particularly preferred, and methyl acrylate is most preferred because it is easily available.

[0014] The mass ratio of the structural unit derived from methyl methacrylate to 100 mass% of the methacrylic resin is preferably 80 to 100 mass%. If it is more than 99 mass%, the heat resistance is improved more than necessary and the solubility property is deteriorated, which is not preferable. Also, if it is less than 80 mass%, the mechanical strength is reduced, which is not preferable. From the viewpoint of heat resistance and solubility property, it is preferably 85 to 99 mass%, and more preferably 90 to 93 mass%.

[0015] In the above methacrylic resin, the other vinyl monomer copolymerizable with methyl methacrylate is a component contained in the copolymer, but is not necessarily contained in the case of a homopolymer. Other vinyl monomers copolymerizable with methyl methacrylate affect solubility and heat resistance. The mass ratio of the structural units derived from other vinyl monomers copolymerizable with methyl methacrylate to 100% by mass of the methacrylic resin is preferably 0 to 20% by mass. From the viewpoint of solubility, it is preferably 1% by mass or more. Also, from the viewpoint of mechanical strength, it is preferably 20% by mass or less. It is more preferably 1 to 15% by mass, and even more preferably 3 to 10% by mass.

[0016] The weight average molecular weight of the methacrylic resin measured by gel permeation chromatography (GPC) is preferably 85,000 to 500,000, more preferably 85,000 to 145,000. From the viewpoint of mechanical strength and amount of resin used when made into artificial marble, it is preferable that it is 85,000 or more. If it is less than 85,000, the amount of methacrylic resin used to make the syrup have a predetermined viscosity increases, which is not preferable. Also, from the viewpoint of stable production of polymerization, it is preferable that it is 145,000 or less. More preferably, it is 90,000 to 130,000, and particularly preferably 95,000 to 110,000.

[0017] The methacrylic resin has a ratio Mw / Mn of the weight average molecular weight Mw to the number average molecular weight Mn measured by gel permeation chromatography (GPC) of 1.7 to 2.5, preferably 1.8 to 2.4, and more preferably 1.9 to 2.2. If it is less than 1.7, the polymerization time becomes longer, which is not preferable. If it exceeds 2.5, the dissolution speed differs depending on the molecular weight, and in particular, undissolved components may aggregate before the high molecular weight components dissolve, resulting in residual dissolution. The weight average molecular weight is measured by GPC. A calibration curve is created in advance from the elution time and weight average molecular weight using a standard methacrylic resin that is available as a reagent with a known monodisperse weight average molecular weight and an analytical gel column that elutes high molecular weight components. The molecular weight of each sample can be measured from the calibration curve.

[0018] The average particle diameter of the methacrylic resin is 150 μm to 250 μm. The smaller the particle diameter, the shorter the dissolution time, so it is 250 μm or less, and if the particle diameter is too small, the beads will scatter a lot, so it is 150 μm or more. The average particle diameter is more preferably 155 to 245 μm, and most preferably 160 to 240 μm. In this specification, the particle size refers to the volume particle size that can be measured by the method described in the Examples below.

[0019] The above methacrylic resin has a standard deviation (SD value) of particle size of 40 to 150 μm, which can prevent pump-up failure and line clogging during slurry transfer when washing polymerized beads. The SD value is more preferably more than 40 μm and less than 150 μm, even more preferably 60 μm or more and less than 150 μm, still more preferably 70 to 140 μm, and particularly preferably 75 to 135 μm. The SD value is represented by the following formula and can be measured by the method described in the Examples below.

number

[0020] The 10% particle size D10 of the methacrylic resin is preferably from 50 μm to 120 μm, and more preferably from 50 μm to 120 μm.

[0021] <Aluminum element content> The content of aluminum element in the methacrylic resin is preferably 1 ppm by mass or more and 50 ppm by mass or less, based on 100% by mass of the methacrylic resin. By making the content of aluminum 1 ppm by mass or more, polymerization can be stabilized. More preferably, it is 1.5 ppm by mass or more, and even more preferably, it is 2 ppm by mass or more. By making it 50 ppm by mass or less, color tone can be improved. More preferably, it is 40 ppm by mass or less, and even more preferably, it is 30 ppm by mass or less. As a method for adjusting the aluminum element content to the above range, there can be mentioned a method in which the pH is adjusted to 3 to 5 with sulfuric acid when removing the suspending agent after the polymerization is completed. The content of aluminum element can be measured by mass spectrometry ICP-MS. The methacrylic resin does not need to contain calcium element.

[0022] <Polymerization method> The methacrylic resin can be produced, for example, by using a monomer constituting a methacrylic resin, a polymerization initiator, a chain transfer agent, a suspending agent, other additives, and the like.

[0023] As the polymerization initiator, when free radical polymerization is used, peroxide-based initiators such as di-t-butyl peroxide, lauryl peroxide, dilauroyl peroxide, t-butylperoxy 2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and azo-based initiators such as azobisisobutyronitrile, azobisisovaleronitrile, and 1,1-azobis(1-cyclohexanecarbonitrile) can be used, which can be used alone or in combination of two or more kinds. These radical initiators can be combined with a suitable reducing agent to be used as a redox-based initiator. The polymerization initiator is generally used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers.

[0024] In the above-mentioned method for producing the methacrylic resin, when the resin is produced by radical polymerization, a commonly used chain transfer agent can be used to adjust the molecular weight. As the chain transfer agent, for example, mercaptans such as n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tristhioglycolate, and pentaerythritol tetrakis(thioglycolate) are preferably used. The chain transfer agent may be used in an amount of 0.001 to 1% by mass relative to 100% by mass of the total mass of the monomers. The amount of the chain transfer agent is determined depending on the desired molecular weight.

[0025] As the polymerization method for the above-mentioned methacrylic resin, it is preferable to use a one-stage suspension polymerization, which gives powdery resin beads, and is advantageous in terms of operation when dissolving an appropriate amount as a thickener for adjusting the syrup to a desired viscosity. Other polymerization methods are not preferred because they do not produce powdery resin beads, and suspension polymerization is preferred because it takes less time to polymerize than emulsion polymerization, which produces a powdery polymer. In particular, the above methacrylic resin is preferably obtained by one-stage suspension polymerization. Two-stage or three-stage polymerization is not preferred because it increases the amount of suspending agent or emulsifier entrained in the beads, resulting in poor color.

[0026] As a method for polymerizing the methacrylic resin, it is preferable to use a method in which a suspending agent having an average particle size of 10 to 40 μm (preferably 13 to 32 μm, more preferably 15 to 29 μm) is dispersed in water and polymerized. Among them, it is preferable to disperse a suspending agent having an average particle size of 10 to 40 μm in water and perform one-stage suspension polymerization. In the above-mentioned method for producing a methacrylic resin, it is preferable to carry out polymerization with the average particle size of the suspending agent dispersed in the suspension polymerization water set to 10 to 40 μm. This makes it possible to control the standard deviation of the particle size of the beads, stabilize the polymerization behavior, reduce the amount of heat removal, and improve productivity. The average particle size of the suspension can be adjusted by appropriately selecting the particle size of the calcium carbonate or aluminum hydroxide powder used. Furthermore, a suspension with an appropriate average particle size can be obtained by mixing powders with different particle sizes.

[0027] In the above-mentioned method for producing a methacrylic resin, it is preferable to adjust the pH of the aqueous phase to a range of 4 to 7. By adjusting the pH within this range, the standard deviation of the particle size of the beads can be controlled, and the polymerization behavior can be stabilized.

[0028] In the above-mentioned method for producing a methacrylic resin, it is preferable to adjust the temperature of the suspending agent to 50°C to 90°C beforehand, and then to put it into the water (50°C to 90°C) in the reactor. For organic suspending agents, the temperature is preferably 50 to 70°C, and more preferably 55 to 65°C. For inorganic suspending agents, the temperature is preferably 50 to 80°C, and more preferably 60 to 75°C. This makes it possible to adjust the average particle size of the beads and its variation.

[0029] Depending on the manufacturing method of the methacrylic resin, it is preferable to use an inorganic suspending agent rather than an organic suspending agent. In the case of an organic suspending agent, the variation in the average particle size of the beads tends to be too small. Here, examples of the organic suspending agent include polyvinyl alcohol, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, gelatin, polyvinyl acetate, etc. The inorganic suspending agent preferably contains an inorganic compound containing calcium and / or aluminum, and examples of the inorganic suspending agent include calcium phosphate such as tricalcium phosphate (calcium phosphate tertiary), calcium carbonate, aluminum hydroxide, etc. In particular, from the viewpoint of stabilizing the polymerization, it is more preferable to contain an inorganic compound containing aluminum. The suspending agent may further contain a suspending aid such as sodium ethylenediaminetetraacetate, sodium lauryl sulfate, polyethylene glycol, etc. The suspending aid may be contained in an amount of 0.01 to 10% by mass relative to 100% by mass of the suspending agent. The above suspending agent is preferably used by mixing it in water together with the monomer raw material.

[0030] The thickener of the present embodiment may be the methacrylic resin obtained by the above-mentioned method as it is, or may be mixed with other methacrylic resin compositions to form a thickener.

[0031] The thickener of the present embodiment can be used as a syrup by dissolving the thickener in methyl methacrylate. The syrup can be polymerized by heating to obtain artificial marble. Furthermore, the thickener of the present embodiment can be used by adding pigments, dyes, and the like to form paints, or by adding adhesives to form adhesives.

[0032] The thickener of the present embodiment shortens the production time without impairing the mechanical strength and durability of conventional artificial marble. It improves the productivity of syrup and reduces the amount of methacrylic resin used, thereby reducing production costs, making it suitable for artificial marble applications. The methacrylic resin which is the thickener of the present invention can be used as a thickener for paints, adhesives, etc., in addition to being used as a syrup for artificial marble. EXAMPLES

[0033] The present invention will be described more specifically with reference to the following examples and comparative examples. It should be noted that Examples 1 to 11 and 13 to 15 are described as reference examples. <Raw materials> The raw materials used were as follows: Methyl methacrylate (MMA): Asahi Kasei Chemicals (containing 2.5 ppm by mass of 2,4-dimethyl-6-tert-butylphenol manufactured by Chugai Boeki as a polymerization inhibitor) Methyl acrylate (MA): Manufactured by Mitsubishi Chemical (containing 14 ppm by mass of 4-methoxyphenol manufactured by Kawaguchi Chemical Industry Co., Ltd. as a polymerization inhibitor) n-Butyl acrylate (BA): Toa Gosei (containing 15 ppm of 4-methoxyphenol as a polymerization inhibitor) n-Octylmercaptan (NOM): Manufactured by Arkema 2-Ethylhexyl thioglycolate (EHTG): Arkema Lauroyl peroxide (LPO): Made by Nippon Oil & Fats Calcium phosphate: Made by Nippon Chemical Industry Co., Ltd. Calcium carbonate: Nitto Funka Kogyo NN#200, average particle size 14.8μm Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, used as a suspension aid Tetrasodium ethylenediaminetetraacetate dihydrate (EDTA): Kishida Chemical Aluminum hydroxide: Nippon Light Metal Co., Ltd.

[0034] [I. Production of thickener] Example 1 -Suspension agent- 5 kg of water, 130 g of aluminum hydroxide having an average particle size of 23 μm, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added to a container equipped with a stirrer to obtain a mixed solution (a2). The obtained mixed solution (a2) was heated to 70°C. The average particle size of the suspension agent in the mixed solution (a2) was 23 μm. Appropriate amounts of dilute sulfuric acid and aqueous sodium hydroxide solution were added to adjust the pH to the range of 4 to 7. -polymerization- 25 kg of water, 3 kg of the above suspending agent, and 21 kg of monomer raw materials having the blending ratio shown in Table 1 were charged into a 60 L reactor, mixed with stirring, and suspension polymerization was carried out for 150 minutes at a reaction temperature of 80°C under the conditions shown in Table 1, essentially completing the polymerization reaction to obtain a polymer. Next, the mixture was cooled to 50°C, and 20% by mass sulfuric acid was charged to dissolve the suspending agent, followed by washing, dehydration, and drying to obtain methacrylic resin beads.

[0035] (Examples 2 to 12, Comparative Examples 1 and 2) Methacrylic resin beads were obtained in the same manner as in Example 1, except that aluminum hydroxides having different particle sizes were used, the suspension agent was adjusted to the range shown in Table 1, and polymerization was performed under the conditions shown in Table 1.

[0036] Example 13 2 kg of water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, 0.39 g of sodium lauryl sulfate, and 2.3 g of EDTA were added to a container equipped with a stirrer to obtain a mixed solution (a1). The obtained mixed solution (a1) was heated to 70°C. The average particle size of the suspension in the mixed solution (a1) was 16 μm. Appropriate amounts of dilute sulfuric acid and aqueous sodium hydroxide solution were added to adjust the pH to 4 to 7. -polymerization- 25 kg of water, 3 kg of the above suspending agent, and 21 kg of monomer raw materials having the blending ratio shown in Table 1 were charged into a 60 L reactor, mixed with stirring, and suspension polymerization was carried out for 150 minutes at a reaction temperature of 80°C under the conditions shown in Table 1, essentially completing the polymerization reaction to obtain a polymer. Next, the mixture was cooled to 50°C, and 20% by mass sulfuric acid was charged to dissolve the suspending agent, followed by washing, dehydration, and drying to obtain methacrylic resin beads.

[0037] Example 14 23 kg of water was placed in a 60 L reactor and heated to 60°C, 630 g of polyvinyl alcohol was dissolved as an organic suspending agent while being heated to 60°C, 21 kg of monomer raw materials in the composition shown in Table 1 were added and mixed with stirring, the reaction temperature of the reactor was increased to 80°C for 150 minutes for suspension polymerization, and then the temperature was raised to 92°C at a rate of 1°C / min, after which the polymerization reaction was essentially completed for 60 minutes. The resulting bead dispersion was washed, dehydrated, and dried to obtain methacrylic resin beads.

[0038] Example 15 Methacrylic resin beads were obtained in the same manner as in Example 1, except that butyl acrylate was used instead of methyl acrylate.

[0039] Comparative Example 3 23 kg of water and 630 g of polyvinyl alcohol as an organic suspending agent were dissolved in a 60 L reactor, and 21 kg of monomer raw materials in the blending ratio shown in Table 1 were added and mixed with stirring, and the reaction temperature of the reactor was raised to 80°C for 150 minutes for suspension polymerization, and then the temperature was raised to 92°C at a rate of 1°C / min, and the mixture was aged for 60 minutes to essentially terminate the polymerization reaction. The resulting bead dispersion was washed, dehydrated, and dried to obtain methacrylic resin beads.

[0040] Comparative Example 4 Methacrylic resin beads were obtained in the same manner as in Example 9, except that the pH during polymerization was 3.8 and the temperature at which the suspending agent was added was 25°C.

[0041] Comparative Example 5 Methacrylic resin beads were obtained in the same manner as in Example 1, except that the average particle size of the suspension agent used was 9 μm.

[0042] (Comparative Examples 6 and 7) Water and a suspending agent with a particle size prepared in the same manner as in Examples 7 and 8 were added to a 60L reactor, and 97% by mass of MMA, 2% by mass of EHTG, and 0.7% by mass of LPO were mixed and stirred as monomer raw materials, and the reaction temperature of the reactor was 80 ° C. for 150 minutes for suspension polymerization, and the polymerization reaction was substantially terminated to obtain polymer (1). Thereafter, the polymerization system containing the above polymer (1) was maintained at 80 ° C. for 60 minutes, and then 97% by mass of MMA, 2% by mass of MA, 0.2% by mass of NOM, and 0.2% by mass of LPO were added as raw materials for polymer (2), and the suspension polymerization was continued at 80 ° C. for 90 minutes, and then the temperature was raised to 92 ° C. at a rate of 1 ° C. / min, and then the mixture was aged for 60 minutes to substantially terminate the polymerization reaction. The weight ratio of polymer (1) to polymer (2) was (1) / (2)=25 / 75. Next, the mixture was cooled to 50 ° C., and 20% by mass of sulfuric acid was added to dissolve the suspending agent, and the mixture was washed, dehydrated, and dried to obtain methacrylic resin beads.

[0043] Comparative Example 8 First, 1.9 g of aluminum sulfate, 3.8 mg of a complexing agent (Trilon B; tetrasodium ethylenediaminetetraacetate dihydrate / BASF), and 19 mg of an emulsifier (K30; sodium salt of C15-paraffin sulfonate / Bayer) were dissolved in 350 g of distilled water with stirring. Next, 1N sodium hydroxide was added at a temperature of about 40°C to adjust the pH value to 5 to 5.5. After that, the mixture was allowed to settle and the aqueous phase was transferred to a 1 L polymerization tank equipped with a stirrer to obtain a suspension (Al(OH)3). In addition, RSO is used as a suspension aid. 3- Na + (R is an alkyl group) was used in combination with the above suspending agent to stabilize the polymerization process described below. Next, 270 g of methyl methacrylate (MMA), 17 g of methyl acrylate (MA), 0.5 g of lauroyl peroxide as a polymerization initiator, and 0.7 g of n-octyl mercaptan as a chain transfer agent were added to the polymerization tank and vigorously stirred, heated to 75°C, and maintained at about 75 to 80°C for 90 minutes. Thereafter, the internal temperature of the polymerization tank was raised to about 90°C, and the temperature condition of 90°C was maintained for 40 minutes to allow the polymerization reaction to proceed. This resulted in the production of a suspension polymer. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent, followed by washing, dehydration, and drying to obtain methacrylic resin beads.

[0044] [II. Physical Properties of Methacrylic Resins] (Weight average molecular weight, molecular weight distribution) The weight average molecular weight and molecular weight distribution of the methacrylic resin beads obtained in the examples and comparative examples were measured using the following apparatus and conditions. Measurement device: gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation. Column: one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series in this order. In this column, high molecular weight compounds elute early, while low molecular weight compounds elute late. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with different molecular weights and known monodisperse peak top molecular weights were used. Peak top molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin. The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin (A) were determined based on the area in the GPC elution curve and the calibration curve of a third-order approximation equation.

[0045] (Volume average particle size, D10) The volume average particle size, SD value, and 10% particle size were measured using the laser scattering method of a Beckman Coulter LS13320.

[0046] (Aluminum content) The aluminum content was measured using a Thermo Fisher ICP-MS (inductively coupled plasma mass spectrometry), model XSERIES2.

[0047] III. Evaluation of thickeners The methacrylic resin beads obtained in the Examples and Comparative Examples were used as a thickener to carry out the following evaluations.

[0048] (dissolution rate) Fill a water bath with a stirrer with water and heat to 60°C. Place 16g of thickener, 64g of methyl methacrylate monomer (for 20wt% thickener) and a stirrer in a 110cc screw-cap bottle (diameter 50mm) and close the lid of the screw-cap bottle. Place the screw-cap bottle in the water bath and start rotating the stirrer to begin measurement. Measure the time it takes for the thickener in the bottle to dissolve in the methyl methacrylate. Completely dissolved within 15 minutes: ◎ (Excellent) Completely dissolved within 20 minutes: Excellent Completely dissolved within 25 minutes: △ (good) If it took more than 25 minutes to dissolve, it was determined to be × (bad).

[0049] (Syrup Viscosity) The measuring equipment used is a B-type viscometer with an SB2 rotor. The syrup prepared using the method described above for dissolution rate is cooled to room temperature (23±3°C) while stirring. Measure 40cc of the syrup liquid into a measuring tube. Place the measuring tube in the viscometer and begin viscosity measurement. Measure the viscosity with a rotor speed of 60 rpm. (If the measurement range is exceeded at 60 rpm, reduce the rotation speed and measure.) Also measure the viscosity with a rotor speed of 6 rpm and compare the viscosity values ​​to determine accuracy. For highly viscous syrups, the amount added must be adjusted when producing the syrup to achieve the appropriate viscosity.

[0050] (Long light path transmittance) The methacrylic resin beads obtained by polymerization were extruded at a resin temperature of 240°C to 250°C using a twin-screw extruder to obtain pellets. In order to easily evaluate the color of the artificial marble, the optical properties of a molded product made only from methacrylic resin were measured. Using the pellets obtained by the above method, a test piece with a thickness of 3 mm, width of 20 mm, and length of 220 mm was produced using an injection molding machine (EC-100SX, manufactured by Toshiba Machine Co., Ltd.) under the conditions of a molding temperature of 280°C and a mold temperature of 60°C. The 220 mm long optical path transmittance was measured from the obtained test piece. The transmittance was evaluated according to the following criteria. The transmittance was measured using a color difference meter (TC-8600A, light source: 10-C, manufactured by Tokyo Denshoku Co., Ltd.) in accordance with JIS K7375. ◎ (Very good): 85% or more ○ (Excellent): 80% or more but less than 85% △(Good): 75% to less than 80% × (defective): Less than 75%

[0051] (Polymerization stability) Regarding polymerization stability, the mass of coarse beads (glass) contained in 21 kg of methacrylic resin beads after polymerization was weighed, and if it was 200g or less, it was rated as "◎ (very excellent)", if it was more than 200g but less than 300g, it was rated as "〇 (excellent)", if it was more than 300g but less than 400g, it was rated as "△ (good)", and if it was more than 400g, it was rated as "× (poor)".

[0052] (Poor pumping when transporting slurry) When the polymerization liquid (slurry) containing the beads obtained after polymerization was transferred to the washing and degassing layer, if no pump-up occurred, it was rated as "◯ (excellent)", if pump-up occurred only once, it was rated as "△ (good)", and if pump-up failure occurred two or more times, it was rated as "× (good)".

[0053] [Table 1] [Industrial Applicability]

[0054] The thickener of the present invention shortens the time required for preparing a syrup and improves the productivity of the syrup, and furthermore, does not impair the mechanical strength and durability of the artificial marble produced using the syrup.

Claims

1. A thickener comprising a methacrylic resin having an Mw / Mn of 1.7 to 2.2, an average particle size of 150 to 250 μm, a standard deviation of the particle size of 40 μm to 150 μm, and an Mw of 412,000 to 500,000.

2. The thickener described in claim 1, wherein the methacrylic resin contains 100 to 80 mass% methyl methacrylate monomer units and 0 to 20 mass% other vinyl monomer units copolymerizable with methyl methacrylate.

3. A thickener described in claim 1 or 2, wherein the 10% particle diameter D10 of the methacrylic resin is 50 μm to 130 μm.

4. A thickener described in any one of claims 1 to 3, wherein the aluminum content in the methacrylic resin is 1 ppm by mass or more and 50 ppm by mass or less.

5. A method for using a thickener, comprising using the thickener described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Resin composition

    JP2006131826A

  • Thickener and method for producing the same

    JP2008174574A

  • Methacrylic resin particle and method for producing the same

    JP2013216764A

  • Resin composition, thickener

    JP2018178076A